Bank versus non-bank credit in the United States, Europe and China - Nicolas Véron (Bruegel, 2013)
In the wake of recent crisis developments in the US and Europe, non-bank credit channels have often been portrayed as 'shadow banking' and have been considered primarily through the lens of the risks they may pose to financial stability. However, the debate about financial system structures remains immature, in large part due to lack of reliable and comparable data. The available evidence actually points towards a correlation between the development of non-bank credit and higher resilience against systemic risk, at least in developed economies. Policy should aim at better statistical information, and at strengthening the infrastructure for the gradual development of sustainable nonbank credit provision.
Keywords: 330